2009
DOI: 10.1271/bbb.90389
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Properties of a Diastereoisomeric Molecular Compound of (2S,3S)- and (2R,3S)-N-Acetyl-2-amino-3-methylpentanoic Acids

Abstract: An X-ray crystal structural analysis revealed that (2S,3S)-N-acetyl-2-amino-3-methylpentanoic acid (Nacetyl-L-isoleucine; Ac-L-Ile) and (2R,3S)-N-acetyl-2-amino-3-methylpentanoic acid (N-acetyl-D-alloisoleucine; Ac-D-aIle) formed a molecular compound containing one Ac-L-Ile molecule and one Ac-D-aIle molecule as an unsymmetrical unit. This molecular compound is packed with strong hydrogen bonds forming homogeneous chains consisting of Ac-L-Ile molecules or Ac-DaIle molecules and weak hydrogen bonds connecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…On the other hand, the C -C bond usually has an anti conformation, because there are no steric interactions near the bond. There are only a few crystal structures containing alloisoleucine (aIle) or its derivatives reported so far (Dalhus & Gö rbitz, 2000;Yajima et al, 2008Yajima et al, , 2009. According to the classification made for isoleucine-containing compounds, structures containing the aIle molecule itself have A-or C-type conformations around the C -C bond, while all crystals containing Ac-aIle exhibit the B-type conformation.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the C -C bond usually has an anti conformation, because there are no steric interactions near the bond. There are only a few crystal structures containing alloisoleucine (aIle) or its derivatives reported so far (Dalhus & Gö rbitz, 2000;Yajima et al, 2008Yajima et al, , 2009. According to the classification made for isoleucine-containing compounds, structures containing the aIle molecule itself have A-or C-type conformations around the C -C bond, while all crystals containing Ac-aIle exhibit the B-type conformation.…”
Section: Figurementioning
confidence: 99%
“…The separation of enantiomeric pairs dl-Ile and dl-alloisoleucine [(2RS,3SR)-(1); dl-aIle] may appear to be easy, but recrystallizing a mixture of four stereoisomers did not give a simple racemate, dl-Ile or dl-aIle, because these stereoisomers form molecular compounds consisting of various combinations of stereoisomers (Dalhus & Gö rbitz, 2000). Previously we revealed that separation of N-acetyl-l-isoleucine (Ac-l-Ile) and N-acetyl-d-alloisoleucine (Ac-d-aIle) by recrystallization is also difficult due to the formation of a molecular compound, whereas their ammonium salts are easily separated by recrystallization from 95% ethanol because they do not form molecular compounds (Yajima et al, 2008(Yajima et al, , 2009. Additionally, some ammonium salts of N-acylated amino acids have been found to exist as conglomerates, which were resolved optically by preferential crystallizations and replacing crystallizations (Shiraiwa et al, 1986(Shiraiwa et al, , 1987(Shiraiwa et al, , 1991ISSN 2052-5206 # 2016 International Union of Crystallography Yajima et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…N-Acetylated amino acids tend to form good crystalline ammonium salts; for example, the ammonium salts of N-acetyl-D-alloisoleucine and N-acetyl-L-isoleucine can be separated from their mixture by recrystallization. 14,15) The networks of hydrogen bonds with the ammonium ions in the crystals of these ammonium salts determine the rigidity of the crystal packing, so that a difference in the side chain conformation of the amino acids would greatly affect their solubility. An ammoniacal aqueous solution of a mixture of Ac-L-Thr and Ac-D-aThr was evaporated to dryness in vacuo to give a mixture of the ammonium salts of Ac-L-Thr and Ac-D-aThr (Ac-L-Thr .…”
mentioning
confidence: 99%